A randomized controlled trial to evaluate genotyping and therapeutic drug monitoring vs. only therapeutic drug monitoring as a strategy for risk minimization in epileptic patients on carbamazepine therapy - Hina Khimsuriya; Sanchita Ambre; Swati More; Vinayak A; Mahesh Belhekar (Recent Trends in Pharmacology)
Objective: Carbamazepine (CBZ) is a widely prescribed antiepileptic drug for the treatment of focal seizures. CBZ gets metabolized by cytochrome enzymes mainly CYP3A5. It is difficult to predict clinically whether a patient is likely to suffer from CBZ toxicity. Hence, we planned to evaluate the use of genotyping and therapeutic drug monitoring (TDM) vs. only TDM in epileptic patients on CBZ as a strategy for risk minimization. Methods: This double-blind, randomized controlled trial included 60 epileptic patients taking carbamazepine, divided into two equal groups. One group’s carbamazepine dosing was guided by genotyping, while the other group’s doses were based solely on clinical judgment.Results: A total of 60 patients were enrolled in the study, in two arms, group A (genotyping and TDM both) and Group B (only TDM), each arm comprising 30 patients. Among the CYP3A5 metabolizer group, the frequency of expressors and non-expressors was (57%) and (43%), respectively. During follow-up visits, at one month, three cases of adverse drug reactions (ADRs) were reported. ADR count decreased to two cases during the three-month follow-up and further reduced to only one case of ADR at the 12-month assessment. It was found that there is no statistically significant association between CYP3A5 metabolizer and ADR occurrence.Conclusion: Adding genotyping to TDM did not significantly reduce the risk of carbamazepine toxicity. However, genotyping may still be useful for patients who exhibit symptoms of toxicity.